Pelaksanaan Sistem Pencatatan, Pelaporan dan Bagi Hasil Antara Pemilik Modal dan Pengelola Usaha Perikanan: (Studi Kasus Desa Nelayan, Sungailiat) - Fitrahadi, Agung (LP2M IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
ABSTRACT Accounting recording and reporting are important things that must be done in a business with the aim of integrating the extent of the development and financial performance of the business. The problem that occurs in this research is the lack of recording and reporting processes carried out by fishery business owners which do not comply with accounting standards because they only record income and expenditure. The system for implementing profit sharing is also not based on mutual agreement, so this can trigger conditions in the business. This research uses qualitative descriptive research as a type of research that describes how fisheries businesses are implemented and the data needed to be able to make financial records according to applicable standards. The data source used in this research is primary data. The data collection techniques used were observation, interviews and documentation. The data analysis technique used is an interactive analysis technique with a data reduction analysis process, data presentation, and drawing conclusions or verification. The results of the research show that recording financial reports in fisheries businesses is still simple and not in accordance with standards because it only records income and expenses, but after implementing SAK EMKM in recording and reporting business finances, there are many benefits obtained by business owners. The implementation of the profit sharingsystem is also only produced by one party, where the profit sharing should be carried out based on joint decisions and agreements